Improving the varieties - WRENmedia (Technical Centre for Agricultural and Rural Cooperation, 2008)
The World Vegetable Centre in Tanzania carries out a variety of activities to increase the cultivation of indigenous food crops. These include the development of new and improved varieties and training for farmers in cultivation and processing. While visiting the Centre?s experimental plots, Lazarus Laiser found out more about this work from research assistant Omary Ijumaa.